1991
DOI: 10.1055/s-2007-1024659
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Skating Techniques and the Diagonal Stride on Heart Rate Responses and Speed in Cross-Country Skiing

Abstract: The purpose of this study was to compare the heart rate responses and the speed of three different skating techniques and the diagonal stride in cross-country skiing. The subjects were ten elite male cross-country ski racers, 16 to 25 years of age. They skied a 3.04-km loop of various terrain four separate times, using a different technique for each trial. A thirty-minute recovery period was allowed between each trial. Heart rate and skiing velocities were analyzed over a flat, an uphill, and a downhill sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 0 publications
4
32
1
Order By: Relevance
“…From the regression equations, the horizontal intercepts were determined. These ''crossover points'' at 4-5 degrees, separate where it was relatively advantageous to use V2 from slopes where it was advantageous to use V1 skating technique skating technique comparisons of physiological responses (e.g., Bilodeau et al 1991;Boulay et al 1994;Millet et al 2003). Thus, little evidence exists providing a physiological basis for technique selection for skating on diverse terrain.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…From the regression equations, the horizontal intercepts were determined. These ''crossover points'' at 4-5 degrees, separate where it was relatively advantageous to use V2 from slopes where it was advantageous to use V1 skating technique skating technique comparisons of physiological responses (e.g., Bilodeau et al 1991;Boulay et al 1994;Millet et al 2003). Thus, little evidence exists providing a physiological basis for technique selection for skating on diverse terrain.…”
Section: Discussionmentioning
confidence: 96%
“…One previous investigation (Bilodeau et al 1991) compared HR response and skiing speed between V1, V2, and V2A skating techniques on snow with elite skiers at race speed around a 3-km track of varying terrain. No significant differences were found in HR values and velocities between the skating techniques on any sections of the course.…”
Section: Physiological Responses On Varying Slopesmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no other study has examined the energy cost of ski or RSS using the V2A technique. However, C s in the three principal skating techniques (V1 skate, V2 skate and V2A) has been indirectly determined from heart rate measurements (Bilodeau et al 1991) and has not been found to be dierent among the three techniques. Thus, it was worth comparing our data with previous C s established in ski skating.…”
Section: Energy Cost Of Roller Ski Skatingmentioning
confidence: 99%
“…In the 1988 Olympics in Calgary, cross-country skiing was performed for the first time distinguishing between two distinct techniques, the classic technique and the free (or skating) technique. The skating technique is much faster than the classic technique, or, for a given speed of skiing, requires less energy and is less tiring, than the classic technique 8 . Nevertheless, this technique was not invented or inspired by biomechanics research, but was developed over decades by a variety of skiing pioneers.…”
Section: What Have We Learnt From Sport Biomechanics?mentioning
confidence: 99%